Pengembangan Teknologi Keberlanjutan Berbasis E-Governance dengan Kecerdasan Buatan Terhadap Kepuasan Masyarakat Terhadap Pemerintah - Hurian Kamela (Owner : Riset dan Jurnal Akuntansi, 2025)
There is still limited development-based sustainability technology based on e-governance with artificial intelligence (AI) on community satisfaction. Previous research only discusses e-governance with artificial intelligence (AI) without comparing with community satisfaction. This research is based on the development of research from (Wurster et al., 2023) to add additional variables regarding the conditions that occur regarding sustainability, governance and Artificial Intelligence (AI). The research design is quantitative. Community survey (questionnaire) cities and districts in the Jabodetabek area The research time is 1 month (September 2024). The results of the study are (1) the community is not very influential on actions regarding technological developments, perhaps because the community already knows enough about technology and (2) the community already understands and understands the development of websites regarding governance, so there is no need to take additional actions.